Construction and Validation of a Classroom Climate Scale: A Mixed Methods Approach - Bilbao-Ramirez, M (Springer Netherlands, 2018)
Students’ perceptions of their classroom climate have been found to relate significantly to students’ learning outcomes. The purpose of the present study was to construct an instrument for assessing elementary-school students’ perceptions of classroom climate, based on a previous instrument that was being used in Chile by a public national school mental health program as a tool for aiding teachers in improving classroom management, but which showed poor psychometric properties. We used a six-staged mixed-methods approach to construct relevant items and dimensions based on this measure and by adapting previously-existing scales. Item development included participatory construction of items involving program officials, focus groups with students, and a pilot study. The final version was administered to a sample of 6813 elementary-school students. Results showed adequate reliability and construct validity, convergent validity with school climate, and divergent validity with peer victimisation. When consequential validity was explored through semi-structured interviews with program officials and school administrators, we found that the instrument was being used as a tool for helping teachers to improve their school climate and management skills. We discuss the importance of constructing instruments using a mixed-methods approach. © 2018, Springer Science+Business Media B.V., part of Springer Nature.